Application and development of indirect measures of free-living energy expenditure - Keytel, Lara (Department of Human Biology, 2016)
The aims of this thesis were to explore the accuracy in measuring free-living total daily energy expenditure (TDEE), by examining existing indirect measures of energy expenditure (EE) measurement and further, developing new techniques, for improved accuracy and application, in population-based studies. In a number of the studies, the research focus is the heart rate (HR) monitoring technique, for TDEE estimation as a result of its low cost and ease of implementation in large population-based studies. This thesis represents a progression from the application of the HR monitoring technique for estimating EE in response to training, or as a means to validate a physical activity recall instrument. However, what is highlighted are the limitations of the existing methodology for estimated TDEE in this way. Therefore, this thesis introduces a novel concept in the HR monitoring technique, incorporating group-based EE equations, and further, by including the effects of the previous minutes HR response on the estimation of EE from HR. Finally, this thesis validates these modifications, using a respiration chamber, purpose-built as a part of this dissertation. It should be noted, however, that in some instances, the thesis was constrained by opportunistic sampling, or the fact that in the case of Chapter 4, the study sample was part of a larger study designed for another purpose. Nevertheless, the outcomes of this research, in particular, the group-based HR-EE prediction equations, have important implications for large population-based epidemiological research concerning physical activity dose-response. Bibliography: p. 227-253.